Respuesta :

Answer:

The answer is 7

Step-by-step explanation:

We have:

if g(x)=5x-3 and h(x)= sqaure root of x.

We have to find (g o h)(4).

(g o h) = g(h(x))

Plug the value of h(x) which is √x in g(x)

g(h(x))= g(√x)

Now plug the value √x in g(x).

g(h(x))= g(√x) = 5√x-3

Now to find (g o h)(4) plug in 4 in place of x

(g o h)(x)=g(h(x))= g(√x) = 5√x-3

(g o h)(4)= g(h(4)) = g(√4) = 5√4-3

Therefore:

(g o h)(4) = 5(2)-3

(g o h)(4) = 10-3 = 7

Thus the answer is 7....

Answer:  [tex](g o h)(4)=7[/tex]

Step-by-step explanation:

Given the function g(x):

[tex]g(x)=5x-3[/tex]

And the function h(x):

[tex]h(x)=\sqrt{x}[/tex]

We need to plug the function  [tex]h(x)=\sqrt{x}[/tex] into the function  [tex]g(x)=5x-3[/tex], in order to find [tex](g o h)(x)[/tex] . Then:

[tex](g o h)(x)=5(\sqrt{x})-3[/tex]

[tex](g o h)(x)=5\sqrt{x}-3[/tex]

Now, in order to find  [tex](g o h)(4)[/tex], we need to substitute [tex]x=4[/tex] into [tex](g o h)(x)=5\sqrt{x}-3[/tex]. Then, this is:

[tex](g o h)(4)=5\sqrt{4}-3[/tex]

[tex](g o h)(4)=10-3[/tex]

[tex](g o h)(4)=7[/tex]